Changes in the vascular flora of the Djurdjura massif (northern Algeria): diachronic comparison of historical data (1854-1965) with current data (1988-2024) - Meddour, Rachid; Sahar, Ouahiba (Biodiversity: Research and Conservation, 2025)
During over 170 years (1854-2024) of botanical explorations in the Djurdjura massif (northern Algeria), several publications were devoted to its flora but never summarized until now. Our study, based on an extensive literature review, aimed to highlight the potential temporal floristic changes and to provide a useful tool for further floristic and taxonomic studies. We created a checklist of historical data (1854-1965) and compared it to current data (1988-2024) on the flora of Djurdjura, to compile finally a comprehensive checklist of the vascular plant species growing in the massif. We found that about 47 floristic studies were carried out in the massif, providing information on 1351 plant species (about 30% of the Algerian flora). Concerning the temporal change, 360 species (26.6% of the total) were newly added after 1988, whereas 269 species (20%) have not been recorded for 60 or more years. The comparative checklist confirms the status of the Djurdjura massif as a centre of floristic diversity and endemism in Algeria. The list can serve as a basis for an inventory of missing species of the Djurdjura massif, targeting the species of high conservation priority.